Is local anaesthesia a favourable approach for transcatheter aortic valve implantation? A systematic review and meta-analysis comparing local and general anaesthesia. Issue 9 (25th September 2017) - Ehret, Constanze; Rossaint, Rolf; Foldenauer, Ann Christina; Stoppe, Christian; Stevanovic, Ana; Dohms, Katharina; Hein, Marc; Schälte, Gereon
Abstract : Objectives: We conducted a systematic review and meta-analysis to identify the potential favourable effects of local anaesthesia plus sedation (LAS) compared with general anaesthesia (GA) in transcatheter aortic valve implantation (TAVI). Methods: Electronic databases (PubMed/Medline, Embase, Cochrane Central Register of Controlled Trials) and the reference lists of eligible publications were screened for randomised controlled trials (RCTs) and observational studies published between 1 January 2006 and 26 June 2016 that compare LAS to GA in an adult study population undergoing TAVI. We conducted study quality assessments using the Cochrane risk of bias tool and structured the review according to PRISMA. A meta-analysis calculating the pooled risk ratios (RRs) and mean differences (MDs) with 95% confidence intervals (CIs) under the assumption of a random-effects model was performed. Statistical heterogeneity was evaluated using the I² statistic and Cochran's Q-test. Results: After database screening, one RCT and 19 observational studies were included in the review. We found no differences between LAS and GA in terms of 30-day mortality, in-hospital mortality and other endpoints that addressed safety and complication rates. LAS was associated with a shorter ICU and hospital stay and with lower rates of catecholamine administration and red blood cell transfusion. New pacemaker implantations occurred more frequently under LAS. The overall conversion rate from LAS to GA was 6.2%. Conclusion: For TAVI, both LAS and GA are feasible and safe. LAS may have some benefits such as increased haemodynamic stability and shorter hospital and ICU stays, but it does not impact 30-day mortality. Since there is a paucity of randomised trial data and the findings are mainly based on observational study data, this review should be considered as a hypothesis-generating article for subsequent RCTs that are required to confirm the potential favourable effects we detected for LAS. Registration number: CRD42016048398 (PROSPERO).